Implementing The Values of Moderation in Committing The Radicalism of Students in Muslimat Islamic Boarding Schools, NU, Central Java - Nurul Azizah; Ahmad Munib; Muhammad Syaichu Zakaria (Communautaire: Journal of Community Service, 2022)
The NU Muslimat Islamic Boarding School is a boarding school under the auspices of the Central Java NU Muslimat Education Foundation. Although in this pesantren, the study of the yellow book is routinely carried out, it is also necessary to strengthen it in countering radicalism. From this service, Islamic boarding schools make efforts to fortify students so that they do not get carried away with radical ideas, namely by conducting seminars and mentoring. From the activities carried out, there are several things that are emphasized for students, namely: strengthening morals, da'wah through social media, strengthening knowledge for provision in preaching, choosing teachers who are clear and credible in their scientific knowledge.